Implementasi Keperawatan dengan Masalah Defisit Nutrisi pada Pasien Tuberkulosis Paru - Mediarti, Devi; Syokumawena, Syokumawena; Prihartini, Desi (Universitas Batanghari Jambi, 2024)
Pulmonary tuberculosis is an infectious disease that transmits the lungs caused by Mycobacterium tuberculosa which has a rod-like shape and is acid-resistant, so it is known as BTA (acid-resistant rods) which is the main factor in Pulmonary Tuberculosis. The type of research used is descriptive in the form of case studies with data collection methods by means of interviews and physical examination. The research subjects were two pulmonary tuberculosis patients with nutritional deficit problems at Muhammadiyah Hospital in Palembang. The nursing implementation approach used includes identification of nutritional status: management of oral hygiene and providing diet education. This study was conducted to compare two respondents who had been given implementation for three days where 1 day was implemented 3 times, namely nutrition management, oral hygiene and diet education and was carried out in the morning. The study showed that after three days of implementation the problem of nutritional deficit experienced by weight patients increased by 1 kg, oral hygiene improved, and knowledge increased.